Influenza B Virus BM2 Protein Is a Crucial Component for Incorporation of Viral Ribonucleoprotein Complex into Virions during Virus Assembly - Imai, Masaki (American Society for Microbiology, 2004)
Influenza B virus contains four integral membrane proteins in its envelope. Of these, BM2 has recently been found to have ion channel activity and is considered to be a functional counterpart to influenza A virus M2, but the role of BM2 in the life cycle of influenza B virus remains unclear. In an effort to explore its function, a number of BM2 mutant viruses were generated by using a reverse genetics technique. The BM2ΔATG mutant virus synthesized BM2 at markedly lower levels but exhibited similar growth to wild-type (wt) virus. In contrast, the BM2 knockout virus, which did not produce BM2, did not grow substantially but was able to grow normally when BM2 was supplemented in trans by host cells expressing BM2. These results indicate that BM2 is a required component for the production of infectious viruses. In the one-step growth cycle, the BM2 knockout virus produced progeny viruses lacking viral ribonucleoprotein complex (vRNP). The inhibited incorporation of vRNP was regained by trans-supplementation of BM2. An immunofluorescence study of virus-infected cells revealed that distribution of hemagglutinin, nucleoprotein, and matrix (M1) protein of the BM2 knockout virus at the apical membrane did not differ from that of wt virus, whereas the sucrose gradient flotation assay revealed that the membrane association of M1 was greatly affected in the absence of BM2, resulting in a decrease of vRNP in membrane fractions. These results strongly suggest that BM2 functions to capture the M1-vRNP complex at the virion budding site during virus assembly.